OH maser emission in the THOR survey of the northern Milky Way - Beuther, Henrik; Klessen, Ralf S.; Glover, Simon (Astronomy and astrophysics, 2019)
Context. OH masers trace diverse physical processes, from the expanding envelopes around evolved stars to star-forming regions or supernovae remnants. Providing a survey of the ground-state OH maser transitions in the northern hemisphere inner Milky Way facilitates the study of a broad range of scientific topics.Aims. We want to identify the ground-state OH masers at ∼18 cm wavelength in the area covered by The HI/OH/Recombination line survey of the Milky Way (THOR). We will present a catalogue of all OH maser features and their possible associated environments.Methods. The THOR survey covers longitude and latitude ranges of and . All OH ground state lines 2Π3/2 (J = 3/2) at 1612 (F = 1−2), 1665 (F = 1−1), 1667 (F = 2−2) and 1720 MHz (F = 2−1) have been observed, employing the Very Large Array (VLA) in its C configuration. The spatial resolution of the data varies between 12.5″ and 19″, the spectral resolution is 1.5 km s−1, and the rms sensitivity of the data is ∼10 mJy beam−1 per channel.Results. We identify 1585 individual maser spots (corresponding to single spectral features) distributed over 807 maser sites (regions of size ∼103 − 104 AU). Based on different criteria from spectral profiles to literature comparison, we try to associate the maser sites with astrophysical source types. Approximately 51% of the sites exhibit the double-horned 1612 MHz spectra typically emitted from the expanding shells of evolved stars. The separations of the two main velocity features of the expanding shells typically vary between 22 and 38 km s−1. In addition to this, at least 20% of the maser sites are associated with star-forming regions. While the largest fraction of 1720 MHz maser spots (21 out of 53) is associated with supernova remnants, a significant fraction of the 1720 MHz maser spots (17) are also associated with star-forming regions. We present comparisons to the thermal 13CO(1-0) emission as well as to other surveys of class II CH3OH and H2O maser emission. The catalogue attempts to present associations to astrophysical sources where available, and the full catalogue is available in electronic form.Conclusions. This OH maser catalogue presents a unique resource of stellar and interstellar masers in the northern hemisphere. It provides the basis for a diverse range of follow-up studies from envelopes around evolved stars to star-forming regions and Supernova remnants.
Gesehen am 14.10.2019